Motorist disorientation syndrome; clinical features and vestibular findings - Ainsworth, Carolyn; Davies, Rosalyn; Colvin, Ian; Murdin, Louisa (Journal of vestibular research, 2023)
BACKGROUND: Motorist Disorientation Syndrome (MDS) is a term used to describe patients who primarily experience symptoms of dizziness/disorientation whilst in a motor car [21]. There is uncertainty about the relevance of vestibular dysfunction and whether this disorder could instead be a visually induced dizziness (VV) or part of a functional disorder similar to Persistent postural perceptual dizziness (PPPD). OBJECTIVE: We present the largest case-series to date of patients whose main complaint is of illusions of movement of self/vehicle when driving, characterising features of this group. METHODS: 18 subjects underwent detailed clinical assessment including validated questionnaires. A subset of patients underwent vestibular function testing. RESULTS: Mean onset age was 42 years, with no gender preponderance. Mean symptom duration was 6.39 years and was significantly longer in women. 50% reported moderate or severe handicap. Vestibular abnormalities were found in 60% of subjects tested. There was no significant difference in VSS total score between those with MDS and vestibular migraine (p = 0.154) with both having higher scores than healthy controls (p = 0.002, 0.000 respectively). CONCLUSIONS: MDS represents consistent symptoms, with high symptom burden, comparable to vestibular migraine. Vestibular deficits were not a consistent feature and similarities to VV and PPPD exist.